2019
DOI: 10.3389/fpsyg.2019.00380
|View full text |Cite
|
Sign up to set email alerts
|

Changes in United States Latino/a High School Students’ Science Motivational Beliefs: Within Group Differences Across Science Subjects, Gender, Immigrant Status, and Perceived Support

Abstract: Science motivational beliefs are crucial for STEM (science, technology, engineering, and math) performance and persistence, but these beliefs typically decline during high school. We expanded the literature on adolescents’ science motivational beliefs by examining: (1) changes in motivational beliefs in three specific science subjects, (2) how gender, immigrant generation status, and perceived support from key social agents predicted differences in adolescents’ science motivational beliefs, and (3) these proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 64 publications
(95 reference statements)
5
19
0
Order By: Relevance
“…Also, interventions offer the opportunity to reveal one-sidedness in research. In today’s view, the assessment of Hsieh et al (2019) is to be agreed that it should be avoided to study the STEM disciplines as if they were a single subject. In fact, the later professions, which build on the various training paths in the STEM disciplines, have very different profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Also, interventions offer the opportunity to reveal one-sidedness in research. In today’s view, the assessment of Hsieh et al (2019) is to be agreed that it should be avoided to study the STEM disciplines as if they were a single subject. In fact, the later professions, which build on the various training paths in the STEM disciplines, have very different profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings are consistent with recent literature. For example, Hsieh, Liu, and Simpkins (2019) found that Latino/a high school students who perceived more support in science had higher science motivational beliefs than those who perceived less support. Additionally, Riggs, Bohnert, Guzman, and Davidson (2010) found that rural Latino/a grade-school youth who regularly attended community-based afterschool programing had developed stronger ethnic identities as well as better concentration and emotion regulation skills than Latino/ a youth who did not regularly attend.…”
Section: Race and Ethnicity And Youth Outcomesmentioning
confidence: 99%
“…However, they were unable to confirm a fall in the general academic self-concept. Similarly, longitudinal studies have shown differential effects in the progression of self-concept depending on background factors: gender [ 21 , 23 , 42 , 43 , 44 ], socio-economic and cultural levels [ 45 , 46 , 47 ], and being an immigrant [ 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%